2006
DOI: 10.1097/01.ccm.0000214292.62276.8e
|View full text |Cite
|
Sign up to set email alerts
|

The two-event model of transfusion-related acute lung injury

Abstract: The objective of this review is to present the two-event model of transfusion-related acute lung injury (TRALI), a life-threatening complication of transfusions that has been the most common cause of transfusion-related death over the past 2 yrs in the United States. The two-event model of TRALI, which is identical to the pathogenesis of the acute respiratory distress syndrome (ARDS), is reviewed and contrasted to antibody-mediated TRALI. Laboratory studies, both in vitro and in vivo, are discussed as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
205
1
7

Year Published

2007
2007
2014
2014

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 204 publications
(215 citation statements)
references
References 100 publications
2
205
1
7
Order By: Relevance
“…43 Alternatively, the 'two-event' model proposes that factors present in transfused stored blood products trigger TRALI in patients in whom endothelial activation is already present due to an initial proinflammatory event, for example, infection, surgery, or trauma. 42 Transfusion-related immunomodulation proposes that deleterious proinflammatory effects result from a complex interplay between transfusion effects, genetic factors, intercurrent illnesses, and inflammatory mediators and effector cells. 44 However, a causal relationship between transfusion and these serious complications is not established.…”
Section: Transfusion and Preoperative Anaemiamentioning
confidence: 99%
“…43 Alternatively, the 'two-event' model proposes that factors present in transfused stored blood products trigger TRALI in patients in whom endothelial activation is already present due to an initial proinflammatory event, for example, infection, surgery, or trauma. 42 Transfusion-related immunomodulation proposes that deleterious proinflammatory effects result from a complex interplay between transfusion effects, genetic factors, intercurrent illnesses, and inflammatory mediators and effector cells. 44 However, a causal relationship between transfusion and these serious complications is not established.…”
Section: Transfusion and Preoperative Anaemiamentioning
confidence: 99%
“…Silliman and his colleagues have shown that this can be a mechanism of acute lung injury, and Gajic and his colleagues have shown that concentrations of lysophospholipids in stored red blood cell units are associated with increased rates of lung injury in intensive care patients [28,29]. However, rates of TRALI are markedly reduced when plasma from women donors is removed from the blood supply, so the role of lysophospholipids in causing clinically important lung injury is not clear [30].…”
Section: Are Stored Red Blood Cells Safe?mentioning
confidence: 99%
“…1,2,4,5 TRALI has been reported to be the result of at least 2 events: the first pertaining to the clinical condition of the patient, and the second to the infusion of antibodies that recognize human lymphocyte antigen (HLA) class I, class II, or granulocyte antigens or the infusion of biological response modifiers, which include both biologically active lipids and soluble CD40 ligand (sCD40L). [6][7][8][9][10][11][12][13][14][15] Standard prestorage leukoreduction (LR) was reported to have decreased TRALI reactions at 1 medical center; however, LR has not affected TRALI incidence in the United States or worldwide. 16,17 To date, there are few RBC mitigation strategies for TRALI.…”
Section: Introductionmentioning
confidence: 99%